The Impacts Of Inbound Tourism Activities And Macroeconomic Variables On Environmental Degradation In Asean-4 - Ekan Widiarso; Regina Niken Wilantari; Agus Luthfi (MediaTrend, 2019)
This study aims to analyze the impacts and causal relationship between inbound tourism activities and macroeconomic variables on environmental degradation and  to analyze the environmental degradation response due to shocks that occur in inbound tourism activities and macroeconomic variables in four countries with the highest international tourist visits in the ASEAN region of Indonesia, Malaysia, Singapore and Thailand known as ASEAN-4 for Periode 1995-2015. The method used in the research is panel vector error correction model (PVECM). The results showed that inbound tourism activities positively influence in the long-term and short-term  environmental degradation in ASEAN-4. Among  macroeconomic variables only gross domestic product (GDP) positively affects environmental degradation in the long term and short term whereas energy consumption only affects environmental degradation in the short term. There is a direct causal relationship of inbound  tourism activity with environmental degradation and environmental degradation with GDP. Energy consumption and environmental degradation manifest  bidirectional causality with a feedback effect. Impulse response function indicates environmental degradation responds negatively to the shocks that occur in Inbound tourism and GDP activities. The positive response is indicated by environmental degradation in case of shock to energy consumption.